A utilização da terceirização no serviço público. Uma análise sobre a produtividade das atividades administrativas realizadas por terceirizados no Instituto Federal de Sergipe - Costa Neto, Valdemar Alves da (2021)
This is a study that aims at analyzing the range of outsourcing in the routine of administrative processes that take place within the federal public service. The idea is to emphasize how productive such a routine can be within the scope of physical processes from the Open Tendering and Contracts Department at the Federal Institute of Sergipe, using criteria of time and rework. The study lists errors that result in reworking, and describes, in days, the amount of time spent in order to carry out pricing surveys in the aforementioned Department. Thus, it proves that there is a connection between reworking and the time spent to accomplish the tasks. Lastly, a manual is offered as the thesis final product, in which some procedures are suggested in order to avoid those errors. Also, a few samples are presented for process flowcharts and pricing surveys and benefit statement reports.